2020
DOI: 10.1108/sgpe-06-2019-0055
|View full text |Cite
|
Sign up to set email alerts
|

The changing postdoc and key predictors of satisfaction with professional training

Abstract: Purpose The postdoctoral position was originally created as a short training period for PhD holders on the path to becoming university professors; however, the single-purpose paradigm of training has evolved considerably over time. The purpose of this paper is to report on the opportunities and challenges faced by postdocs as they navigate this complex training period. Design/methodology/approach To better understand the changes in postdoctoral training the Canadian Association of Postdoctoral Scholars – l’A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 33 publications
0
30
0
Order By: Relevance
“…While autonomy certainly is a component of the professoriate, some postdoctoral scholars possess an unrealistic view of how autonomy plays out in practice. It is often coupled with managing a heavy workload and chronic stress, with intense pressures to secure external funding and publish to make successful progress toward tenure (Eddy and Gaston-Gayles, 2008; Hudson et al , 2018; Kachchaf et al , 2015; Van Benthem et al , 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While autonomy certainly is a component of the professoriate, some postdoctoral scholars possess an unrealistic view of how autonomy plays out in practice. It is often coupled with managing a heavy workload and chronic stress, with intense pressures to secure external funding and publish to make successful progress toward tenure (Eddy and Gaston-Gayles, 2008; Hudson et al , 2018; Kachchaf et al , 2015; Van Benthem et al , 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Although some aspiring professors may face negative career outlooks, postdoctoral positions that boost confidence and self-efficacy predict one’s desire to remain in academia (van der Weijden et al , 2016). Encouraging relationships with supervisors and other colleagues also tend to buffer postdoctoral scholars from the stress and burnout that push hopeful academics to turn to industry or governmental employment opportunities (Kim et al , 2019; Van Benthem et al , 2020). Other factors found to draw individuals to the professoriate include an attraction to the life of an academic (Lindholm, 2004); the perception of research autonomy, independence and individual expression (Gibbs and Griffin, 2013; Lindholm, 2004); and a desire to help others (Gibbs and Griffin, 2013; Mendez et al , 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Boeren et al, drawing on 23 papers related to ECRs, summarily defined an ECR as an individual 'with less than 10 years of experience from the start of their PhD ' (2015: 69). This group thus includes postdocs who are simultaneously attempting to build their professional research profile, gain recognition, establish networks, obtain funding, and earn a salary within a narrow time frame (van Benthem et al, 2020). Both Boeren et al (2015) and Forbrig (2020) claimed that their definition was the same as that indicated by the European Commission (EC, 2011).…”
Section: Who Are Early Career Researchers and Why Does It Matter?mentioning
confidence: 99%
“…Generally, in such laboratories, the success of publication output tends to be assigned to the supervisor or PI, who would likely not have achieved this success had there not been a formidable team, engendering a Matthew Effect (Teixeira da Silva, 2021a). Even though some postdocs perform a disproportional amount of work that accounts for the productivity of a laboratory, their careers might still be at risk, especially if there are more postdocs than there are available positions, causing a 'postdoc pile-up' (van Benthem et al, 2020). With an amplified publication curriculum vitae and prestige, funding may be amplified (Bol et al, 2018), but funding tends to be received by the supervisor rather than the ECR.…”
Section: Who Are Early Career Researchers and Why Does It Matter?mentioning
confidence: 99%